A systematic review and meta-analysis of randomized controlled trials on the effects of magnesium supplementation on insulin sensitivity and glucose control. (September 2016) - Simental-Mendía, Luis E.; Sahebkar, Amirhossein; Rodríguez-Morán, Martha; Guerrero-Romero, Fernando
Graphical abstract: Abstract: A systematic review and meta-analysis was conducted to evaluate the effect of oral magnesium supplementation on insulin sensitivity and glucose control in both diabetic and non-diabetic individuals. PubMed-Medline, SCOPUS, Web of Science and Google Scholar databases were searched (from inception to November 25, 2015) to identify RCTs evaluating the effect of magnesium on insulin sensitivity and glucose control. A random-effects model and generic inverse variance method were used to compensate for the heterogeneity of studies. Publication bias, sensitivity analysis, and meta-regression assessments were conducted using standard methods. The impact of magnesium supplementation on plasma concentrations of glucose, glycated hemoglobin (HbA1c), insulin, and HOMA-IR index was assessed in 22, 14, 12 and 10 treatment arms, respectively. A significant effect of magnesium supplementation was observed on HOMA-IR index (WMD: ⿿0.67, 95% CI: ⿿1.20, ⿿0.14, p  = 0.013) but not on plasma glucose (WMD: ⿿0.20 mmol/L, 95% CI: ⿿0.45, 0.05, p  = 0.119), HbA1c (WMD: 0.018 mmol/L, 95% CI: ⿿0.10, 0.13, p  = 0.756), and insulin (WMD: ⿿2.22 mmol/L, 95% CI: ⿿9.62, 5.17, p  = 0.556). A subgroup analysis comparing magnesium supplementation durations of <4 months versus ⿥4 months, exhibited a significant difference for fasting glucose concentrations ( p  < 0.001) and HOMA-IR ( p  = 0.001) in favor of the latter subgroup. Magnesium supplementation for ⿥4 months significantly improves the HOMA-IR index and fasting glucose, in both diabetic and non-diabetic subjects. The present findings suggest that magnesium may be a beneficial supplement in glucose metabolic disorders.